Functional variants in the sucrase–isomaltase gene associate with increased risk of irritable bowel syndrome. Issue 2 (21st November 2016) - Henström, Maria; Diekmann, Lena; Bonfiglio, Ferdinando; Hadizadeh, Fatemeh; Kuech, Eva-Maria; von Köckritz-Blickwede, Maren; Thingholm, Louise B; Zheng, Tenghao; Assadi, Ghazaleh; Dierks, Claudia; Heine, Martin; Philipp, Ute; et al.
Abstract : Objective: IBS is a common gut disorder of uncertain pathogenesis. Among other factors, genetics and certain foods are proposed to contribute. Congenital sucrase–isomaltase deficiency (CSID) is a rare genetic form of disaccharide malabsorption characterised by diarrhoea, abdominal pain and bloating, which are features common to IBS. We tested sucrase–isomaltase ( SI ) gene variants for their potential relevance in IBS. Design: We sequenced SI exons in seven familial cases, and screened four CSID mutations (p.Val557Gly, p.Gly1073Asp, p.Arg1124Ter and p.Phe1745Cys) and a common SI coding polymorphism (p.Val15Phe) in a multicentre cohort of 1887 cases and controls. We studied the effect of the 15Val to 15Phe substitution on SI function in vitro. We analysed p.Val15Phe genotype in relation to IBS status, stool frequency and faecal microbiota composition in 250 individuals from the general population. Results: CSID mutations were more common in patients than asymptomatic controls (p=0.074; OR=1.84) and Exome Aggregation Consortium reference sequenced individuals (p=0.020; OR=1.57). 15Phe was detected in 6/7 sequenced familial cases, and increased IBS risk in case–control and population-based cohorts, with best evidence for diarrhoea phenotypes (combined p=0.00012; OR=1.36). In the population-based sample, 15Phe allele dosage correlated with stool frequency (p=0.026) and Parabacteroides faecal microbiota abundance (p=0.0024). The SI protein with 15Phe exhibited 35% reduced enzymatic activity in vitro compared with 15Val (p<0.05). Conclusions: SI gene variants coding for disaccharidases with defective or reduced enzymatic activity predispose to IBS. This may help the identification of individuals at risk, and contribute to personalising treatment options in a subset of patients.